Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1210/endocr/bqab193
|View full text |Cite|
|
Sign up to set email alerts
|

Transient Dexamethasone Loading Induces Prolonged Hyperglycemia in Male Mice With Histone Acetylation in Dpp-4 Promoter

Abstract: Glucocorticoid causes hyperglycemia which is common in patients with or without diabetes. We experience prolonged hyperglycemia even after the discontinuation of glucocorticoid use. In the present study, we examined time course of blood glucose level in the patients of our hospital who received transient glucocorticoid treatment. In addition, the mechanism of prolonged hyperglycemia was investigated by using dexamethasone (Dexa)-treated mice and cultured cells. The blood glucose level in glucose tolerance test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…Glucocorticoid treatment is often only temporary to maintain an appropriate benefit-risk ratio. Despite their clear clinical benefit, glucocorticoids can worsen preexisting diabetes and cause insulin resistance and hyperglycemia, leading to “metasteroid diabetes.” Uto et al ( 1 ) report that hyperglycemia-induced by 2 years of glucocorticoid treatment persists for 2 years after steroid discontinuation despite antidiabetic treatment, including exogenous insulin. Delineating the cause of this sustained metabolic reprogramming and memory may improve diagnostics, treatment tailoring, and provide insight into the long-term effects of glucocorticoid treatment.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Glucocorticoid treatment is often only temporary to maintain an appropriate benefit-risk ratio. Despite their clear clinical benefit, glucocorticoids can worsen preexisting diabetes and cause insulin resistance and hyperglycemia, leading to “metasteroid diabetes.” Uto et al ( 1 ) report that hyperglycemia-induced by 2 years of glucocorticoid treatment persists for 2 years after steroid discontinuation despite antidiabetic treatment, including exogenous insulin. Delineating the cause of this sustained metabolic reprogramming and memory may improve diagnostics, treatment tailoring, and provide insight into the long-term effects of glucocorticoid treatment.…”
mentioning
confidence: 99%
“…Glucocorticoids reduce insulin sensitivity, promote hepatic gluconeogenesis, and reduce glucose transport in skeletal muscle. Uto et al ( 1 ) used a transient dexamethasone-loading mouse model, which revealed that the prolonged hyperglycemia and glucose intolerance were accompanied by impaired in vivo glucose-stimulated insulin secretion. Glucagon-like peptide 1 (GLP-1) is a gut-derived incretin hormone released into circulation upon nutrient intake that stimulates insulin secretion from the pancreas in a glucose-dependent manner.…”
mentioning
confidence: 99%
See 3 more Smart Citations